The use of pacifiers for non-nutritive sucking in the South African neonatal intensive care units: ethical considerations - Van der Westhuyzen, Annelie (My University, 2015)
The World Health Organization (WHO) launched the Baby Friendly Hospital Initiative (BFHI) in an attempt to increase breastfeeding rates amongst infants. This initiative is focussed on eliminating hospital practices that could influence breastfeeding success. One such practice is the provision of pacifiers to breastfeeding infants which is highlighted in step 9 of BFHI’s 10 steps to successful breastfeeding. Pacifiers are known to potentially cause nipple confusion and a decrease in milk supply. In this report I argue that the use of pacifiers for preterm infants in the Neonatal Intensive Care Units (NICUs) is ethically justified, since the benefits of pacifier use for preterm infants in the NICU outweigh the potential influence on breastfeeding success. The benefits of pacifier use for NNS for preterm infants include self-regulation, pain management and a faster maturation of the suckswallow- breathe (SSB) coordination. An established SSB coordination is needed for successful oral feeding. In the NICU, preterm infants face unique challenges. These challenges include separation of the mother-infant dyad, frequent painful stimuli and breastfeeding difficulties that can be attributed to a poor SSB coordination. This paper suggests that pacifiers can be used to mitigate and improve the effects of these challenges. In this paper I used the principlism framework, consisting of the four bioethical principles namely autonomy, beneficence, non-maleficence and justice to highlight the constitutional conflicts and ethical dilemmas when considering the benefits of pacifier use and its potential influence on breastfeeding. I argue that hospitals with a baby friendly accreditation have ethically justified reasons to provide pacifiers for preterm infants in their NICUs